Decision-making in the capital budgeting context: effects of type of decision aid and increases in information load - Maren Hartmann; Barbara E. Weißenberger (Journal of Business Economics, 2023)
This paper sheds light on the question of whether a rules-based or general principles-based decision aid is preferable in the context of increased information load by experimentally investigating how different types of decision aids interact with increases in information load in a structured capital budgeting decision-making task. The experiment employed a 20.167em0.167em2 between-subjects design and was run in a course on management control systems with 136 master's degree students at a German university. Subjects were tasked with reviewing investment proposals that contained differing amounts of information (low vs. high information load, i.e., irrelevant information cues in addition to those relevant for the decision). The second manipulation referred to the type of decision aid—either a detailed, rules-based capital budgeting guideline with clear cut-off rates, or the advice to employ generally accepted criteria for investment decision-making. The dependent variables investigated were perceived task complexity, decision accuracy, and decision confidence. Increases in information load and provision of a decision aid based on general principles led to an increase in perceived task complexity. There was only limited evidence for experimental conditions affecting decision accuracy, but the group of subjects relying on the rules-based capital budgeting guideline reported significantly higher decision confidence.
Keywords: M41; D83; C91; D91; 650; Information overload; Decision-making; Principles- vs. rules-based decision aid; Capital budgeting